Incidental uptake of 18F-fluorocholine (FCH) in the head or in the neck of patients with prostate cancer - Hodolič, Marina (Radiology and oncology (Ljubljana), 2014)
Background. Positron emission tomography-computed tomography (PET/CT) with 18F-fluorocholine (FCH) is routinely performed in patients with prostate cancer. In this clinical context, foci of FCH uptake in the head or in the neck were considered as incidentalomas, except for those suggestive of multiple bone metastases. Case reports. In 8 patients the incidental focus corresponded to a benign tumour. The standard of truth was histologyin two cases, correlative imaging with MRI in four cases, 99mTc-SestaMIBI scintigraphy, ultrasonography and biochemistry in one case and biochemistry including PTH assay in one case. The final diagnosis of benign tumoursconsisted in 3 pituitary adenomas, 2 meningiomas, 2 hyperfunctioning parathyroid glands and 1 thyroid adenoma. Malignancy was proven histologically in 2 other patients: 1 papillary carcinoma of the thyroid and 1 cerebellar metastasis.Conclusions. To the best of our knowledge, FCH uptake by pituitary adenomas or hyperfunctioning parathyroidglands has never been described previously. We thus discuss whether there might be a future indication for FCH PET/CT when one such tumour is already known or suspected: to detect a residual or recurrent pituitary adenoma aftersurgery, to guide surgery or radiotherapy of a meningioma or to localise a hyperfunctioning parathyroid gland. Inthese potential indications, comparative studies with reference PET tracers or with 99mTc-sestaMIBI in case of hyperparathyroidism could be undertaken.
Keywords: adenom; FCH; hyperparathyroidism; incidentaloma; kopičenje radioindikatorja; meningioma; PET/CT; pituitary adenoma; prostata; prostate; računalniška tomografija; rak (medicina); thyroid adenoma